Pilot aerobic exercise intervention for youth at‐risk for serious mental illness. Issue 3 (26th May 2020) - Corbett, Syl; Farris, Megan S.; MacQueen, Glenda; Addington, Jean
Abstract: Background: This study was conducted as a pilot exercise intervention in youth at‐risk for serious mental illness (SMI). The objectives were to examine the feasibility of an exercise intervention and to determine what improvement was observed, following participation in a moderate‐ to high‐intensity aerobic exercise programme. Methods: Forty‐four male and female youth at‐risk for SMI were recruited. Participants completed clinical, lifestyle and fitness assessments prior to and following a 16‐week moderate‐ to high‐intensity aerobic exercise intervention. Sixty‐minute exercise sessions were held three times per week. Results: Forty‐one participants completed the entire intervention and assessments; thus, the retention rate was 93.2%. Exercise participants achieved a mean of 98.3 (standard deviation (SD) 26.1) minutes/week of high‐intensity and a mean of 32.8 (SD 8.7) minutes/week of moderate‐intensity aerobic exercise over the course of 16 weeks. Improvements in aerobic fitness and body composition as well as reductions in anxiety and depression were observed after the exercise intervention. Conclusion: Aerobic exercise is a feasible and sound intervention strategy in youth at‐risk for SMI. Further research is required to expand upon these initial findings and develop knowledge of the mechanisms, optimum dose and factors that influence the efficacy of exercise.